171k views
5 votes
Solve for x: 3x − 2 > 5x + 10.

x > 6
x < 6
x < −6
x > −6

User Vinitius
by
5.5k points

2 Answers

4 votes

Answer:

x < -6

Explanation:

3x − 2 > 5x + 10

<=> 5x + 10 < 3x -2

<=> 5x - 3x < - 2 - 10

<=> 2x < -12

<=> x < -12/2

=> x < -6

User Kim Major
by
5.3k points
7 votes

Answer:

x < −6

Explanation:

In inequalities, the division by a negative number results in change of the sign. That is from less than to greater than and vice versa.

Therefore,

3x − 2 > 5x + 10.

= 3x - 5x > 2 +10

= -2x > 12

= x < -6

The sign changes as defined above.

User Lubi
by
6.7k points